Tracing metamorphism, exhumation and topographic evolution in orogenic belts by multiple thermochronology: a case study from the Nizke Tatry Mts., Western Carpathians - Danisik, M.; Kadlec, J.; Glotzbach, C.; Weisheit, A.; Dunkl, I.; Kohut, M.; Evans, Noreen; Orvosova, M.; McDonald, Bradley (Birkhäuser Verlag, Basel, 2011)
A combination of four thermochronometers [zircon fission track (ZFT), zircon (U–Th)/He (ZHe), apatite fission track (AFT) and apatite (U–Th–[Sm])/He (AHe) dating methods] applied to a valley to ridge transect is used to resolve the issues of metamorphic, exhumation and topographic evolution of the Nizke Tatry Mts. in the Western Carpathians. The ZFT ages of 132.1 ± 8.3, 155.1 ± 12.9, 146.8 ± 8.6 and 144.9 ± 11.0 Ma show that Variscan crystalline basement of the Nizke Tatry Mts. was heated to temperatures >210 °C during the Mesozoic and experienced a low-grade Alpine metamorphic overprint. ZHe and AFT ages, clustering at ~55–40 and ~45–40 Ma, respectively, revealed a rapid Eocene cooling event, documenting erosional and/or tectonic exhumation related to the collapse of the Carpathian orogenic wedge. This is the first evidence that exhumation of crystalline cores in the Western Carpathians took place in the Eocene and not in the Cretaceous as traditionally believed. Bimodal AFT length distributions, Early Miocene AHe ages and thermal modelling results suggest that the samples were heated to temperatures of ~55–90 °C during Oligocene–Miocene times. This thermal event may be related either to the Oligocene/Miocene sedimentary burial, or Miocene magmatic activity and increased heat flow. This finding supports the concept of thermal instability of the Carpathian crystalline bodies during the post-Eocene period.